ПРОБЛЕМА НАЦІОНАЛЬНОЇ САМОСВІДОМОСТІ МАЙБУТНІХ СПЕЦІАЛІСТІВ ВИЩОГО ПЕДАГОГІЧНОГО ЗАКЛАДУ (Педагогіка вищої та середньої школи, 2001)
This article deals with the problem of forming students’ national consciousness in higher educational institutions. The author gives the data obtained as a result of verifying the experiments connected with the investigation of this problem.